2012
DOI: 10.1186/1471-2164-13-431
|View full text |Cite
|
Sign up to set email alerts
|

A moderate increase in ambient temperature modulates the Atlantic cod (Gadus morhua) spleen transcriptome response to intraperitoneal viral mimic injection

Abstract: BackgroundAtlantic cod (Gadus morhua) reared in sea-cages can experience large variations in temperature, and these have been shown to affect their immune function. We used the new 20K Atlantic cod microarray to investigate how a water temperature change which, simulates that seen in Newfoundland during the spring-summer (i.e. from 10°C to 16°C, 1°C increase every 5 days) impacted the cod spleen transcriptome response to the intraperitoneal injection of a viral mimic (polyriboinosinic polyribocytidylic acid, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 72 publications
5
52
0
Order By: Relevance
“…normality), and were presented as mean ± SE. For QPCR fold-change calculation, overall fold up-regulation was calculated as 2 A − B as in Hori et al (2012), where A is the mean of log 2 transformed RQ from an experimental diet (e.g. 100CO or 100COSEFM) group, and B is the mean of log 2 transformed RQ from the control diet (FO) group.…”
Section: Statistical Analyses Of Growth and Qpcr Datamentioning
confidence: 99%
“…normality), and were presented as mean ± SE. For QPCR fold-change calculation, overall fold up-regulation was calculated as 2 A − B as in Hori et al (2012), where A is the mean of log 2 transformed RQ from an experimental diet (e.g. 100CO or 100COSEFM) group, and B is the mean of log 2 transformed RQ from the control diet (FO) group.…”
Section: Statistical Analyses Of Growth and Qpcr Datamentioning
confidence: 99%
“…In Atlantic cod (G. morhua), two isoforms of IRF10 splice variants were identified with notable difference in the timing and intensity of response to poly(I:C) and/or bacterial challenge. The expression of both two IRF10 isoforms was significant up-regulate by poly(I:C), and the highest expression of the long isoform in response to poly(I:C) challenge occurred at 24 hpi at 10 C and 6 hpi at 16 C, while the greatest increase of short isoform was observed at 6 hpi at both 10 C and 16 C [29,30]. Regarding bacterial challenge, the significant increase in the expression of long isoform was observed only at 24 hpi (2.4 fold) and the expression of the short one occurred at 6 hpi at 10 C (1.37 fold) and 16 C (2.7 fold) and 24 hpi at 10 C (1.48 fold), indicating that these two variants may have distinct roles in cod immune response [29,30].…”
Section: Discussionmentioning
confidence: 96%
“…The expression of both two IRF10 isoforms was significant up-regulate by poly(I:C), and the highest expression of the long isoform in response to poly(I:C) challenge occurred at 24 hpi at 10 C and 6 hpi at 16 C, while the greatest increase of short isoform was observed at 6 hpi at both 10 C and 16 C [29,30]. Regarding bacterial challenge, the significant increase in the expression of long isoform was observed only at 24 hpi (2.4 fold) and the expression of the short one occurred at 6 hpi at 10 C (1.37 fold) and 16 C (2.7 fold) and 24 hpi at 10 C (1.48 fold), indicating that these two variants may have distinct roles in cod immune response [29,30]. In the present study, the highest increase in the expression of grouper IRF10 at mRNA level was also observed at 6 hpi after poly(I:C) treatment, which is quite consistent with the result observed in flounder and zebrafish and the shorter isoform of cod IRF10, implying that grouper IRF10 has an important role in antiviral response as reported in other teleost fish and chicken [25,27,28].…”
Section: Discussionmentioning
confidence: 96%
“…Recently, Dios et al [15] demonstrated that zebrafish (Danio rerio) treated with poly (I:C) have different expression profiles of immune-related genes such as Toll-like receptor 3 (TLR3), Mx, and interferon regulatory factor 3 (IRF3) between low (15 C) and high (28 C) temperatures. Interferon stimulatory gene 15 (ISG15) expression in Atlantic cod after poly (I:C) injection was higher at 16 C than 10 C at 6 hpi [9]. Likewise, we previously reported that Mx expression in sevenband grouper injected with poly (I:C) was regulated by temperature [10].…”
Section: Introductionmentioning
confidence: 84%